How to tell a story and other essays - Twain, Mark, 1835-1910 (Floating Press, 2008)
In How to Tell a Story and Other Essays, iconic American author Mark Twain discusses his own experience as a writer and his personal style. In various essays in the collection he attacks a contemporary of his, defends a maligned dead woman and defends ordinary citizens against the insults of train conductors.